2019
DOI: 10.1186/s12885-019-6136-9
|View full text |Cite
|
Sign up to set email alerts
|

A pair-wise meta-analysis highlights circular RNAs as potential biomarkers for colorectal cancer

Abstract: Background Circular RNAs (circRNAs) have emerged as a special subset of endogenous RNAs that are implicated in tumorigenesis and cancer progression. Herein we aim to carry out a meta-analysis to evaluate the clinicopathologic, diagnostic and prognostic significance of circRNA expression in colorectal cancer (CRC). Methods A systematic search of online databases was performed for original articles published in English, which investiga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Previous meta-analyses have revealed that the diagnostic AUCs of circRNAs in gastric cancer (GC), 42 colorectal cancer (CRC), 43 hepatocellular carcinoma (HCC), 44 we have found that circRNAs yield higher accuracy in differentiating BC from healthy individuals than that from adjacent noncancerous controls. Nonetheless, the number of samples included in the subgroup analysis has curtailed compared with that in the whole analysis, and the conclusion needs to be confirmed by more large sample size studies in the future.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Previous meta-analyses have revealed that the diagnostic AUCs of circRNAs in gastric cancer (GC), 42 colorectal cancer (CRC), 43 hepatocellular carcinoma (HCC), 44 we have found that circRNAs yield higher accuracy in differentiating BC from healthy individuals than that from adjacent noncancerous controls. Nonetheless, the number of samples included in the subgroup analysis has curtailed compared with that in the whole analysis, and the conclusion needs to be confirmed by more large sample size studies in the future.…”
Section: Discussionmentioning
confidence: 74%
“…Previous meta‐analyses have revealed that the diagnostic AUCs of circRNAs in gastric cancer (GC), 42 colorectal cancer (CRC), 43 hepatocellular carcinoma (HCC), 44 and non‐small‐cell lung cancer (NSCLC) 45 reach 0.78, 0.79, 0.86, and 0.86, respectively, with a SEN, SPE, and AUC of circRNAs of 0.72, 0.74, and 0.79 in all malignancies 46 . In our analysis, a total of 2438 BC patients (73.49% of stage 0, I, and II in the diagnostic studies) were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 26 ] HR and 95%CI were combined based on multivariate Cox hazard regression analysis. [ 27 ] The sensitivity and metaregression tests were used to identify the underlying causes of heterogeneity. Publication bias was quantitatively judged by Deeks’ funnel plot asymmetry test, Begg and Egger tests.…”
Section: Methodsmentioning
confidence: 99%
“…11 Previous study reported that circRNAs play important roles during the progression and development of cancers including gastric cancer, prostate cancer and colorectal cancer. [12][13][14] Furthermore, circRNAs play important roles in ovarian tumor growth via functioning as oncogenes or tumor suppressor genes. 9,15 In addition, some circRNAs have been found to regulate gene expression through functioning as competing endogenous RNAs (ceRNAs) at the transcriptional or post-transcriptional level.…”
Section: Introductionmentioning
confidence: 99%